Violent political conflicts in Afghanistan and their relations with Pakistan's and Iran's Afghanistan policies 2001-2017 - Atifmal, Atiqullah
This research examined Pakistan's and Iran's policies towards Afghanistan after the US invasion in 2001. Pakistan's and Iran's foreign policy patterns and trends in Afghanistan since 2001 beyond official and diplomatic undertones have been that of support for the civil war, instability and violent political conflict. The conceptual framework composed of national interests and foreign policy analysis guided this research. The study used qualitative method of data collection and interpretive method of data analysis. Primary sources of data collection among others included, author's memoirs official documents, policy papers, speeches of Afghan, Pakistani and Iranian political leaders and security institutions and unstructured interview with selected personalities concerned with Pakistan and Iran's policies towards Afghanistan. The study among others found that the insurgency and militancy in Afghanistan are fought by the Afghans are supported and sustained by powers with vested interests; Pakistan and Iran always perceived a strong Afghan state as a threat; both Pakistan and Iran were bent on supporting a government in Kabul that is politically, economically, and militarily dependent on policy thinking in Islamabad and Tehran; that there is a huge trust deficit between the Afghan and Pakistani and Iranian political elites; and the post-Taliban Afghan elites and groups do not have a national consensus over major national issues and priorities. The study recommends that political violence in Afghanistan can end when Pakistan and Iran are willing to accept Afghanistan as an independent state and respect its sovereignty. Furthermore, Pakistan and Iran must support Afghan-led and Afghan-owned peace process in Afghanistan. This policy shift in Pakistan's and Iran's foreign policies towards Afghanistan requires a decisive intervention of the US supported by China, Russia, Saudi Arabia and India by demanding Pakistan and Iran to cooperate in ending violence in Afghanistan and stopping support for insurgency.